Bromide in Patients with SCN1A-Mutations Manifesting as Dravet Syndrome - Lotte, Jan; Haberlandt, Edda; Neubauer, Bernd; Staudt, Martin; Kluger, Gerhard Josef (Neuropediatrics, 2012)
We report a retrospective analysis of bromide therapy in 32 patients suffering from Dravet syndrome with SCN1A-mutations who received bromide. After 3 months of bromide treatment, 26 patients (81%) showed a relevant improvement with a reduction of seizure frequency by >50% (>75%) in 18 (12) patients (56 and 37%, respectively). After 12 months, we observed a reduction of >50% (>75%) in 15 (9) patients (47 and 28%, respectively). Long-term response was noted in 18 patients (56%). Adverse reactions were mainly mild or moderate leading to treatment termination in 5/32 patients; no aggravation was reported. We conclude that bromide holds promise in patients with SCN1A-mutations suffering from Dravet syndrome.
Keywords: SCN1A-mutation; Dravet syndrome; bromide; long-term efficacy